Tensile strength of two soldered alloys (Minalux and Verabond2) - Mir Mohammad Rezaee S; Taghavi Nia A (Tehran University of Medical Sciences, 2002)
Recently. Minalux alloy, a base metal free from Be, has been presented on the market while no special soldering has been recommended for it. On the other hand, based on the manufacturer's claim, this alloy is similar to Verabond2. The aim of this study was to investigate the tensile strength of Minalux and Verabond2, soldered by Verasolder. Twelve standard dambble shape samples, with the length of 18 mm and the diameter of 3mm, were prepared from each alloy. Six samples of each alloy were divided into two pieces with carboradom disk. Soldering gap distance was 0.3mm, measured by a special jig and they were soldered by Verasolder alloy. Six other samples, of both Iranian and foreign unsoldered alloys were considered as control group. Then samples were examined under tensile force and their tensile strength was recorded. Two- way variance analysis showed that the tensile strength of Minalux alloy and Verabond2 were not statistically significant (Verasoler 686, Minalux 723), but after soldering, such difference became significant (Minalux 308, Verabond2 432). Verabond2 showed higher tensile strength after soldering.